Iran and the International Community (RLE Iran A). - Ehteshami, Anoush (Routledge Library Editions: Iran., 2012)
In this book experts examine the main features of Iran's foreign policy from 1980 - 1990, assessing relations with the UN, the superpowers, Europe, the GCC and Iraq. Although the Islamic revolution made Iran a significant force in the international arena, it is argued that the ending of the Cold War and the rise of Iraq as the dominant power in the Gulf are now creating a very different set of foreign policy challenges and options.